2014
DOI: 10.1039/c4cc05404k
|View full text |Cite
|
Sign up to set email alerts
|

SmI2–H2O-mediated 5-exo/6-exo lactone radical cyclisation cascades

Abstract: The SmI2-H2O reagent system mediates challenging 5-exo/6-exo lactone radical cascade cyclisations that deliver carbo[5.4.0]bicyclic motifs in a diastereoselective, one-pot process that establish two new carbocyclic rings and four stereocentres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…After the solvent had evaporated, (5-iodopent-1-yn-1-yl)benzene was isolated (1.474 g, 91%) as a brown liquid, which matched previously reported spectra. Without any further purification, we proceeded to the next step: 52 1 H NMR (400 MHz, CDCl 3 ) δ 7.41 (ddd, J = 6.2, 4.5, 2.7 Hz, 2H), 7.34−7.09 (m, 3H), 3.37 (t, J = 6.8 Hz, 2H), 2.56 (t, J = 6.7 Hz, 2H), 1.22 (t, J = 7.0 Hz, 2H).…”
Section: The Of Organic Chemistrymentioning
confidence: 99%
“…After the solvent had evaporated, (5-iodopent-1-yn-1-yl)benzene was isolated (1.474 g, 91%) as a brown liquid, which matched previously reported spectra. Without any further purification, we proceeded to the next step: 52 1 H NMR (400 MHz, CDCl 3 ) δ 7.41 (ddd, J = 6.2, 4.5, 2.7 Hz, 2H), 7.34−7.09 (m, 3H), 3.37 (t, J = 6.8 Hz, 2H), 2.56 (t, J = 6.7 Hz, 2H), 1.22 (t, J = 7.0 Hz, 2H).…”
Section: The Of Organic Chemistrymentioning
confidence: 99%
“…For example, homologation of the tether at the α position grants access to [5.4.0]bicyclic tertiary alcohol products 63, albeit in lower yield because of the challenging nature of the 6-exo-trig cyclization that terminates the cascade sequence (Scheme 27A). 62…”
Section: Cascade Processes Utilizing Follow-up Cyclizationsmentioning
confidence: 99%
“…Preliminary studies showed the feasibility of re-engineering the cascade cyclizations to deliver a range of molecular architectures. For example, homologation of the tether at the α position grants access to [5.4.0]­bicyclic tertiary alcohol products 63 , albeit in lower yield because of the challenging nature of the 6-exo-trig cyclization that terminates the cascade sequence (Scheme A) . Furthermore, allenyllactones 64 undergo “right then right” cascade cyclizations upon treatment with SmI 2 –H 2 O to deliver bridged bicyclic tertiary alcohol products 65 in moderate yields (Scheme B) …”
Section: Exploiting Radical Anions Derived From Carboxylic Acids In C...mentioning
confidence: 99%